Enhancement of γ-aminobutyric acid production by Lactobacillus plantarum Taj-Apis362 and its bioactivities in yoghurt with antihypertensive effect on rats - Hussin, Farah Salina (2021)
γ-aminobutyric acid (GABA) has been well known to play a critical role in the central and peripheral nervous systems in terms of blood pressure regulation. Numerous foods have been reported to naturally contain GABA; for example, fruits and vegetables but in trace amounts. Therefore, this study aims to produce high GABA naturally via fermentation in yoghurt by using lactic acid bacteria (LAB), at a low glutamate concentration while eliminating the use of cofactor, pyridoxal-5' -phosphate (PLP) which is typically needed during GABA production. The GABA-producing ability of three novel strains of lactic acid bacteria (L. plantarum Taj-Apis362, assigned as UPMC90, UPMC91, and UPMC1065) co-cultured with starter culture in yoghurt was evaluated. A combination of UPMC90 + UPMC91 with starter culture symbiotically revealed the most prominent GABA-producing effect. Response surface methodology revealed the optimized fermentation conditions at 39.0 °C, 7.25 h, and 11.5 mM glutamate substrate concentration to produce GABA-rich yoghurt (29.96 mg/100g) with desirable pH (3.93) and water-holding capacity (63.06%). GABA content was further enhanced by the addition of simple sugars and commercial prebiotics where simple sugars induced more GABA production (42.83–58.56 mg/100g) compared to the prebiotics (34.19–40.51 mg/100g), with 2% glucose promoting the most GABA production in yoghurt (58.56 mg/100g) surpassing the control sample with added PLP (48.01 mg/100 g). The yoghurt prepared with glucose also had the highest probiotic count (9.31 log CFU/g). The effect of sugars and prebiotics on the rheological properties of yoghurt were not significant when compared to standard yoghurt in terms of consistency index (K), yield stress and dynamic oscillatory measurements. However, the addition of FOS and inulin showed significant effects on firmness, consistency and cohesiveness in texture profile analysis. The microstructure of yoghurt supplemented with inulin, FOS, and GOS was found to have more crosslinks interconnected, forming a compact protein network with small serum pores, than standard yoghurt and also those supplemented with glucose, sucrose, and fructose. A comparison study on the presence of bioactive components showed significant differences in peptide content and ACE-inhibitory activity between GABA rich yoghurt and standard yoghurt. The antioxidant activity measured by using ferric reducing ability of plasma (FRAP) assay was significantly higher for GABA-rich yoghurt (53.64 μM) than for standard yoghurt (47.61 μM) and the results were vice versa in 2,2'-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay. Metabolomics profiling using 1H-NMR was also conducted and revealed different metabolite concentrations of amino acid, sugar and organic acid in GABA-rich and standard yoghurt. Simulated gastrointestinal digestion of this GABA‑rich yoghurt showed a non‑significant reduction in GABA content and probiotic viability, demonstrating the resistance towards a highly acidic environment (pH 1.2). Refrigerated storage up to 28 days improved GABA production (83.65 mg/100 g) compared to fresh GABA‑rich yoghurt prepared on day 1. In in vivo study, a blood pressure-lowering efficacy at 0.1 mg/kg GABA dosage (equivalent to 30 mg/kg GABA-rich yoghurt) was demonstrated in spontaneous hypertensive rats and no toxicity was observed for GABA-rich yoghurt up to 1500 μg/mL of concentration via the zebrafish model. These results successfully mitigate the over-use of glutamate substrate and omit the use of PLP cofactor at a shorter fermentation time during GABA enhancement in yoghurt, offering an economical approach to produce a probiotic-rich dairy food that also has high bioactive components with an antihypertensive effect.